Respostas

2013-04-23T19:10:26-03:00

3x--3-2x         =          5x-15

-----------         =----------------------

 5                                   6

 

 

 

6,(x-3) =   5, (5x-15)

 

6x-18 = 25x - 75

 

75-18= 25x - 6x

57= 19x

x = 57/19 = 3

 

 

Solução (3)

 

2013-04-23T19:22:39-03:00

3x-3-2x         5x-15

________= ________

5                             6

 

 

x-3 =    5x-15

____    ____

5                6

 

6x-15   = 10x - 75

_____________

         30 (corta o 30)

 

6x-15 = 10x - 75 

6x - 10x = -75 + 15

-4x = - 60 ( vezes -1)

4x = 60

x= 60/4

x=15